Genetically predicted alterations in thyroid function are associated with the risk of benign prostatic disease - Huang, Yan; Chen, Cheng; Zhou, Wanqing; Zhang, Qian; Zhao, Yanfei; He, Dehao; Ye, Zhi; Xia, Pingping (Frontiers in Endocrinology, 2023)
Benign prostatic diseases (BPD), such as benign prostate hyperplasia (BPH) and prostatitis, have a detrimental effect on a man's quality of life. Interestingly, contradictory results are frequent in observational studies exploring the association between thyroid function and BPD. In this study, we aimed to explore whether there is a causal genetic association between them through Mendelian randomization (MR) analysis. We used publicly available summary statistics from the Thyroidomics Consortium and 23andMe on TSH (54,288 participants), FT4 (49,269 participants), subclinical hypothyroidism (3,440 cases and 49,983 controls), overt hypothyroidism (8,000 cases and 117,000 controls), and subclinical hyperthyroidism (1,840 cases and 49,983 controls) to screen for instrumental variables of thyroid function. Results for BPD such as prostatic hyperplasia (13,118 cases and 72,799 controls) and prostatitis (1,859 cases and 72,799 controls) were obtained from the FinnGen study. The causal relationship between thyroid function and BPD was primarily assessed using MR with an inverse variance weighting (IVW) approach. In addition, sensitivity analyses were performed to test the robustness of the results. We found that TSH [OR (95% CI) = 0.912(0.845-0.984), p =1.8 x 10-2)], subclinical hypothyroidism [OR (95% CI) = 0.864(0.810-0.922), p =1.04 x 10-5)], and overt hypothyroidism [OR (95% CI) = 0.885 (0.831-0. 944), p =2 x 10-4)] had a significant effect on genetic susceptibility to BPH, but hyperthyroidism [OR (95% CI) = 1.049(0.990-1.111), p =1.05 x 10-1)] and FT4 [OR (95% CI) = 0.979(0.857-1.119), p = 7.59 x 10-1)] had no effect. TSH [OR (95% CI) =0.823(0.700-0.967), p = 1.8 x 10-2)] and overt hypothyroidism [OR (95% CI) = 0.853(0.730-0.997), p = 4.6 x 10-2)] significantly influenced the prostatitis, whereas FT4 levels [OR (95% CI) = 1.141(0.901-1.444), p = 2.75 x 10-1)], subclinical hypothyroidism [OR (95% CI) =0. 897(0.784- 1.026), p = 1.12 x 10-1)], and hyperthyroidism [OR (95% CI) = 1.069(0.947-1.206), p = 2.79 x 10-1)] did not have a significant effect. Our study suggested that for genetically predicted BPH and prostatitis, the presence of hypothyroidism and TSH levels influence their risk of occurrence. This provides new insights into the causal relationship between thyroid function and BPD.